Effects of the Mitochondria-Targeted Antioxidant Mitoquinone in Murine Acute Pancreatitis - Wei Huang; Nicole Cash; Li Wen; Peter Szatmary; Rajarshi Mukherjee; Jane Armstrong; Michael Chvanov; Alexei V. Tepikin; Michael P. Murphy; Robert Sutton; David N. Criddle (Hindawi Limited, 2015)
Although oxidative stress has been strongly implicated in the development of acute pancreatitis (AP), antioxidant therapy in patients has so far been discouraging. The aim of this study was to assess potential protective effects of a mitochondria-targeted antioxidant, MitoQ, in experimental AP using in vitro and in vivo approaches. MitoQ blocked H2O2-induced intracellular ROS responses in murine pancreatic acinar cells, an action not shared by the control analogue dTPP. MitoQ did not reduce mitochondrial depolarisation induced by either cholecystokinin (CCK) or bile acid TLCS, and at 10 µM caused depolarisation per se. Both MitoQ and dTPP increased basal and CCK-induced cell death in a plate-reader assay. In a TLCS-induced AP model MitoQ treatment was not protective. In AP induced by caerulein hyperstimulation (CER-AP), MitoQ exerted mixed effects. Thus, partial amelioration of histopathology scores was observed, actions shared by dTPP, but without reduction of the biochemical markers pancreatic trypsin or serum amylase. Interestingly, lung myeloperoxidase and interleukin-6 were concurrently increased by MitoQ in CER-AP. MitoQ caused biphasic effects on ROS production in isolated polymorphonuclear leukocytes, inhibiting an acute increase but elevating later levels. Our results suggest that MitoQ would be inappropriate for AP therapy, consistent with prior antioxidant evaluations in this disease.